PRICAI 2000, topics in artificial intelligence : 6th Pacific Rim International Conference on Artificial Intelligence, Melbourne, Australia, August 28-September 1, 2000 : proceedings - Mizoguchi, Riichiro; Slaney, J. K. (John K.) (Lecture notes in computer science ;, 2000)
This book constitutes the refereed procedings of the 6th Pacific Rim International Conference on Artificial Intelligence, PRICAI 2000, held in Melbourne, Australia, August/September 2000. The 72 revised full papers presented together with 44 poster-abstracts were carefully reviewed and selected from a total of 207 submissions coming from 25 countries. The papers are organized in topical sections on logic and foundations, induction and logic programming, reinforcement learning, machine learning, knowledge discovery, Bayesian networks, beliefs and intentions in agents, autonomous agents, agent systems, genetic algorithms, genetic programming, constraint satisfaction, neural networks, Markov decision processes, robotics, image processing and pattern recognition, natural language, AI in web technology, intelligent systems, and AI and music.